THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE AND FAMILY SUPPORT WITH EFFORTS TO PREVENT UNWANTED PREGNANCY (KTD) DUE TO SEXUALLY FREE (Study on Young Girls at Sman 1 Cimarga Rangkas Bitung Lebak Banten in 2023) - Rohmayati Rohmayati; Nanik Yuliwati (International Journal of Medicine and Health, 2023)
Background : Adolescents are indeed very vulnerable to promiscuity, this situation is very concerning, from this behavior unwanted pregnancy often occurs which has a negative impact on socio-economic health and others. Therefore, prevention efforts can be made as early as possible based on the knowledge and attitude and support from parents.One of the things that happens to young women is the many cases of unwanted pregnancies (KTD). Like at SMAN 1 Cimarga Rangkas Bitung Lebak Banten in 2022 there were 2 students who were pregnant out of wedlock, and lots of various deviant sexual behaviors. Writing purpose : Aims todetermine the relationship between knowledge, attitudes and family support with efforts to prevent adverse events due to free sex in young women at SMAN 1 Cimarga Rangkas Bitung Lebak Banten in 2023. Research methods : This study used quantitative and analytic methods with a cross sectional approach. A sample of 72 young women was obtained using proportional random sampling. The data was obtained using a questionnaire that had been tested for validity, then the data was analyzed using a frequency distribution and chi square test. Research result : The knowledge of female adolescents is mostly good (56.9%), positive attitude (58.3%), family support including support (59.7%) and prevention of adverse events in young women due to free sex (66.7%). There is a relationship between knowledge and efforts to prevent adverse events due to free sexual intercourse in young women (p value 0.000), there is a relationship between attitudes and efforts to prevent unwanted pregnancy due to free sexual intercourse in young women (p value 0.000) and there is a relationship between family support and efforts to prevent unwanted pregnancy due to free sex in young women (p value 0.000). Conclusions and recommendations : Knowledge, attitude, family support related toefforts to prevent adverse events due to free sex in young women. Therefore, adolescents can increase knowledge and increase positive attitudes and do better pregnancy prevention.